Financial Ratios and Capital Structure: Moderating Effect of Firm Size - Cindy Salawatan Trisyanti; Wida Purwidianti; Erna Handayani; Alfalisyado Alfalisyado (Akuisisi : Jurnal Akuntansi, 2025)
The study aimed to examine how profitability, liquidity, asset structure, and solvency impact capital structure when moderated by firm size. This research is quantitative research using financial/annual reports with the population of the property and real estate companies listed on the Indonesia Stock Exchange in 2020-2023. The sampling technique used was purposive sampling so that 178 data were obtained with an observation period of four years, processed with IBM SPSS Statistics 26. The findings of this study indicate that liquidity and solvency significantly and positively affect theÂ capital structure, firm size can strengthen liquidity and solvency affect theÂ capital structure, profitability and asset structure have no effect on capital structure, and firm size cannot moderate profitability and asset structure affect the capital structure. The contribution of this research can be useful for investors and companies in making funding decisions. It is recommended for further researchers to repeat the study with a larger dataset or use data from different periods to validate the results.